PENGEMBANGAN PEMBANGKIT LISTRIK TENAGA MIKRO HIDRO (PLTMH) DENGAN POMPA AIR MENGGUNAKAN TURBIN PELTON SKALA PROTOTYPE - Irfan Ardiansyah; Basuki (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Indonesia has large water energy potential, with 75,000-76 . 000 MW of air energy that can be utilized. One way to exploit this potential is with a Micro Hydro Power Plant (PLTMH). PLTMH is a small-scale power plant that uses river water to produce electricity. This research aims to develop a PLTMH prototype in the Energy Conversion Laboratory of the Mechanical Engineering Study Program, Faculty of Engineering, Hasyim Asy'ari University. It is hoped that this prototype can help students understand better about PLTMH energy conversion. The research method used is research and development (R&D). The research results show that the PLTMH prototype developed has frame dimensions of 500 mm width, 1000 mm height and 1200 mm length. This prototype has been validated with results of 89% for functional tests and 100% for feasibility tests. Based on the research results, it can be concluded that: The PLTMH prototype developed has been successfully created and can operate smoothly. The PLTMH prototype has been validated with excellent results, showing that this prototype meets the functional and feasibility criteria.